Glucose-C(14) Metabolism of Dormant and Activated Ascospores of Neurospora - Budd, Kenneth (1966)
Budd, Kenneth (The University of Michigan, Ann Arbor), Alfred S. Sussman, and Frederick I. Eilers. Glucose-C(14) metabolism of dormant and activated ascospores of Neurospora. J. Bacteriol. 91:551–561. 1966.—Dormant and activated ascospores of Neurospora tetrasperma, incubated in C(14)-labeled glucose, absorb and metabolize this sugar. At the same time, up to 55% of the CO(2) production from endogenous substrates is quenched, whereas total CO(2) production is unchanged. Glucose-carbon appears in CO(2), lipids, and ethyl alcohol-soluble and -insoluble material in both dormant and activated ascospores, although the proportions entering these fractions differ in the two groups of spores. With few exceptions, the identifiable intermediates of glucose metabolism are the same in dormant and activated ascospores, indicating that the principal pathways may be identical. During glucose metabolism, dormant ascospores accumulate a nondialyzable, ethyl alcohol-soluble polymer, or polymers, which is either absent from activated spores or present in much smaller amounts. This material contains glucose, ribose, and at least nine amino acids, and may represent precursors of more complex cell material which accumulate because of an enzymatic deficiency in the dormant spore. Radioactivity is incorporated into all fractions of the dormant spores and into CO(2) without a noticeable lag, indicating that most, if not all, of the enzymes for glucose utilization are present. A lag in incorporation is observed in the activated spores, which most probably is due to rapid endogenous production of glucose from trehalose, resulting in dilution of lable. After absorption of labeled glucose, two pools of trehalose are found in dormant spores, one of which is extractable without breaking the spores, and the other, only after the spores are disintegrated. The widely differing specific radioactivity of the two pools indicates that these are separated in the intact spore.